Development of a Noninvasive Method for Early Stage Lung Cancer Diagnosis Based on Methylation Analysis of SHOX2 and PTGER4. Issue 2 (7th January 2019) - Yin, Wei; Zhu, Junjie; Gonzalez‐Rivas, Diego; Liu, Ming; Song, Nan; Xu, Xinnan; Jiang, Gening; Yang, Yang
Abstract: The oncogenesis of lung cancer is often accompanied by significant methylation abnormalities, which offer a practical and efficient method for diagnosis. Considering that early diagnosis is of great significance for improving the therapeutic effect of lung cancer, the current study aims to develop a diagnostic method based on methylation level analysis. A specific quantitative polymerase chain reaction system, which quantitatively determines the methylation level of SHOX2 and PTGER4 genes, is constructed. Samples used in this reaction system are obtained through noninvasive means, that is, by enriching cell‐free DNA from peripheral blood. 1303 peripheral blood samples, 475 samples from healthy controls and 828 from patients with nonmalignant lung diseases or lung cancer are collected. The specificity and sensitivity of this system to diagnose early stage lung cancer (stage Tis0 and I) are 95.4% and 68.6%, respectively. When the system is used to detect samples from healthy controls or benign lung disease patients, the specificity and sensitivity reach as high as 96.0% and 92.4%, respectively. These findings suggest that screening early stage lung cancer lesions through determining the methylation of SHOX2 and PTGER4 genes in cell‐free DNA represents a promising tool for clinical application. Abstract : A cell‐free DNA (cfDNA) based early stage lung cancer diagnosis approach is successfully developed. The determination of the methylation state of SHOX2 and PTGER4 genes contributes to the screening and diagnosis of early stage lung cancer. The specificity and sensitivity of this approach to diagnose early stage lung cancer (stage Tis0 and I) is 95.4% and 68.6%, respectively, for 1303 peripheral blood samples.